Insertion of Sustainability in the Administration Course: Theoretical essay (Research, Society and Development, 2021)
Objective: foster reflections on the inclusion of environmental and sustainable themes in the Administration Course. Method: it consists of a theoretical essay developed from an analysis of the scientific production of the theme. Results: not all Administration Courses have a specific curricular component that encompasses environmental education. Some seek to propose activities that involve the subject and make it possible to interact with other courses, transposing disciplinarity in a journey towards achieving the transdisciplinarity advocated in the National Curriculum Guidelines for Environmental Education. Final considerations: in the Administration Course the subject is usually present, but greater investments and articulations are still needed to transcend the presentation in isolated disciplines and start to occur in a transdisciplinarity way, taking advantage of the various training spaces, such as research groups and projects and extension projects. Another possibility is the transversal approach to environmental education, so that it can be discussed with students from the initial semesters.